2020
DOI: 10.3390/rs12233999
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Spatio-Temporal Landscape Changes from VHR Images in Three Different Permafrost Areas in the Western Russian Arctic

Abstract: Our study highlights the usefulness of very high resolution (VHR) images to detect various types of disturbances over permafrost areas using three example regions in different permafrost zones. The study focuses on detecting subtle changes in land cover classes, thermokarst water bodies, river dynamics, retrogressive thaw slumps (RTS) and infrastructure in the Yamal Peninsula, Urengoy and Pechora regions. Very high-resolution optical imagery (sub-meter) derived from WorldView, QuickBird and GeoEye in conjuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 94 publications
1
8
0
Order By: Relevance
“…In the Bovanenkovo gas field, Yamal Peninsula, the affected areas substantially increased from 70 km 2 in 1984 to 836 km 2 in 2011 in association with the oil exploration and development activities [65]. The industrial transformation continued at this site where the length of gas pipelines increased by 7.4 times between 2004 and 2016 [66]. Similarly, in northern Alaska the oil field development had affected 34% of the mapped area from 1949 to 2011 [67].…”
Section: Change Dynamics Around the Yueya Lakementioning
confidence: 89%
“…In the Bovanenkovo gas field, Yamal Peninsula, the affected areas substantially increased from 70 km 2 in 1984 to 836 km 2 in 2011 in association with the oil exploration and development activities [65]. The industrial transformation continued at this site where the length of gas pipelines increased by 7.4 times between 2004 and 2016 [66]. Similarly, in northern Alaska the oil field development had affected 34% of the mapped area from 1949 to 2011 [67].…”
Section: Change Dynamics Around the Yueya Lakementioning
confidence: 89%
“…Often real-time surveillance applications [35,36] have urgent constraints that require fast data analytics in analyzing the situations quickly and accurately. Land scanning by high resolution imaging of satellite generates a large amount of real-time data [37,38], which is continuous and dynamic-situations and landscapes change.…”
Section: Discussionmentioning
confidence: 99%
“…RTS are abrupt permafrost disturbances that result from slope failure after thawing of ice-rich permafrost which is found either in ice-rich Yedoma regions (Strauss et al, 2017) or formerly glaciated areas that still contain permafrost-preserved buried glacial ice (Kokelj et al, 2017). Initiated by fluvial processes, thermo-erosion or mass wasting following heavy precipitation events and the exposure of ice-rich permafrost, RTS expand successively into the landscape with retrogressive growth of a steep headwall and the increase of a slump floor, rapidly and irreversibly changing the landscape (Ardelean et al, 2020;Kokelj and Jorgenson, 2013;Séjourné et al, 2015). RTS vary in size, ranging from under 0.15 ha to mega slumps of 52 ha and more (Ramage et al, 2017;Kokelj et al, 2015;Lacelle et al, 2015;Günther et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previous RTS studies covered a range of local to regional spatial extents and annual to decadal temporal resolutions. Commonly, RTS dynamics were estimated using very high resolution remote sensing imagery for limited local spatial extents from a selected number of points in time, restricted by availability of very high resolution imagery, allowing assessment of individual or a cluster of few RTS (Ardelean et al, 2020;Balser et al, 2014;Pollard, 2005, 2008;Lantz and Kokelj, 2008;Luo et al, 2019;Segal et al, 2016;Séjourné et al, 2015;Mu et al, 2020). Based on manually digitised RTS extents and limited fieldwork, these studies found increasing rates of RTS activity for varying time periods.…”
Section: Introductionmentioning
confidence: 99%